The Stabilizing Expenditure Rule in Poland—Simulations for 2014–2040. Issue 4 (3rd July 2016) - Korniluk, Dominik
Abstract : The stabilizing expenditure rule (SER) imposed on the general government (GG) sector in Poland has been in force and binding since 2014. According to this rule, approximately 90 percent of GG expenditure is allowed to grow, at the most, in line with the real medium-term GDP, and the maximum expenditure growth rate is lowered if there is excessive debt or deficit, or the GG balance does not meet the medium-term objective. A series of stochastic simulations has been constructed that allows for the assessment of how the SER will affect the most important public finance indicators in the period between 2014 and 2040. In addition, this article analyzes the consequences of the lowering of debt thresholds in the SER's correction mechanism due to the pension system reform implemented in Poland in 2014, and the amendment to the formula in 2015, and predicts how the fiscal reaction function may change after the introduction of the SER in Poland.